Clinical and Demographic Profile of Covid-19 Infected Pregnant Women admitted in Obstetric Ward - Thapa, Meena; Karki, Dilasha; Maharjan, Sujata; Lama, Lakpa Dolma (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To evaluate the severity of the infection among pregnant women in an urban area of Nepal during the first surge in COVID-19 cases in Nepal in the year 2020. Methods: This is a retrospective and descriptive study carried out at Department of Obstetrics and Gynecology in Kathmandu Medical College, Kathmandu, Nepal, from August 2020 to January 2021. All the Covid infected pregnant women admitted in Obstetric ward for various presenting symptoms were included. Results: Among 52 Covid-19 positive pregnant women admitted for various obstetrical and medical complaints, 90.38% were asymptomatic at the time of admission. Those who were symptomatic (9.61%) had mild form of infection. Majority of infected women were admitted in the month of October and November with most common presentation being women in labour (48.07 %). Conclusions: Pregnant women with SARS Covid-19 infection has no greater threat to their health.